(untitled) (Journal of Hama University, 2022)
The nursing profession is an occupation with a high level of emotional labor. So, it is important to identify the level of emotional intelligence among nursing students for an effective nursing leadership and quality nursing care. Aim: the aim of this study was - to identify the level of emotional intelligence among students of -Faculty of Nursing at Tishreen University. Methods: a descriptive cross-sectional study was performed using a convenience sample of 179 third- year students of Faculty of Nursing at Tishreen University in Lattakia. A structured questionnaire on emotional intelligence was measured, it consisted of five subscales as follows: perception of emotion, managing of emotions, regulations of emotions, empathy, social skills. Results: the findings of this study showed that the level of emotional intelligence among the study sample was high; the majority of nursing students (76.5%) was high in the overall emotional intelligence scale, and (23.5%) were moderate. -However, the highest mean score was that for empathy ( (%79.3, and the lowest score was for emotional management (51.4%). Recommendations:–this current study recommends to -conduct longitudinal studies to study the factors that affect the level of emotional intelligence for students. Also, developing emotional skills such as organizing and managing emotions through workshops or lectures or training, and enhancing the social communication environment for students by providing social support.